Analysis of the Influence of Digital-Based Internal Communication on Employee Job Satisfaction in the Digitalization Era - Baldan Alamanda; Rahmadanil Tesardo Pasla; Sandi Nasrudin Nibowo (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
In the era of digitalization, internal communication based on digital platforms is very important to increase employee productivity. This study examines how digital communication affects work performance by considering communication ethics, accessibility of digital devices, and clarity of information. This study used a cross-sectional survey method using a quantitative approach with 150 respondents from the fields of technology, manufacturing, and law. Data analysis was carried out using SPSS using multiple linear regression. The results showed that digital communication had a positive and significant impact on work performance (R2 = 0.739; p < 0.001), clarity of information (M = 4.35), accessibility (M = 4.40), and engagement (M = 4.25) as the main factors. However, 32% of respondents experienced information overload, especially in the technology sector. This highlights the importance of flexible digital communication strategies, such as hybrid and notification-based approaches. This study contributes to the development of organizational communication strategies that are more effective and responsive to the challenges of the digital era.